2023
DOI: 10.5951/jresematheduc-2020-0232
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Flexibility Using Comparing Solution Strategies and Classroom Discussion: Effects of Two Professional Development Programs

Abstract: This article shows that enabling teachers to integrate comparing solution strategies into their teaching fosters student flexibility in algebra. We designed two professional development (PD) programs that either focused exclusively on comparing solution strategies, or additionally introduced the accountable talk approach to guiding productive classroom discussions. The effects of both PD programs were investigated in an experimental field study (N = 39 teachers, 739 students). In both experimental groups, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
5
0
3
Order By: Relevance
“…Their contribution adds a field study component to earlier work by Rittle-Johnson and Star (2007) that documented the efficacy of contrasting cases in algebra in laboratory settings. Rüede et al (2023) found that when teachers were supported by professional development, students exposed to comparing solution strategies showed better gains in strategy flexibility and procedural fluency. The study contributes more evidence to the area of instructional improvement, suggesting that teacher professional development adds value to materials development.…”
Section: The Articles In This Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Their contribution adds a field study component to earlier work by Rittle-Johnson and Star (2007) that documented the efficacy of contrasting cases in algebra in laboratory settings. Rüede et al (2023) found that when teachers were supported by professional development, students exposed to comparing solution strategies showed better gains in strategy flexibility and procedural fluency. The study contributes more evidence to the area of instructional improvement, suggesting that teacher professional development adds value to materials development.…”
Section: The Articles In This Issuementioning
confidence: 99%
“…The second pair of articles, Rüede et al (2023) and Clements et al (2023), could be described as cases of the documenting improvement efforts type, because they both assess the merit of approaches to improve aspects of the practice of mathematics education, albeit at different scales. Rüede et al (2023) situate their article in the context of algebra instruction and investigate the efficacy of an instructional approach that engages students in comparing solution strategies. Their contribution adds a field study component to earlier work by Rittle-Johnson and Star (2007) that documented the efficacy of contrasting cases in algebra in laboratory settings.…”
Section: The Articles In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The talk sequence is only productive when the productive talk moves result in an interaction that meets the intended demands of the moves. However, various findings show that the number of productive talk moves can serve as a proxy for the productivity of classroom talk: The number of productive talk moves is positively related to the number, length, and content quality of student turns as well as to student performance (Chen et al, 2020;O'Connor et al, 2017;Pauli & Reusser, 2015;Rüede et al, 2023).…”
Section: Use Of Productive Talk Movesmentioning
confidence: 99%
“…There are recent studies that have demonstrated the theoretically expected effects of orchestrating productive classroom talk on student performance in mathematics (Chen et al, 2020;O'Connor et al, 2015;Pauli & Reusser, 2015;Rüede et al, 2023), mostly in secondary school. However, there are also some studies that found no effects on student performance (in science and mathematics: Pehmer et al, 2015;in literature: Reznitskaya et al, 2012).…”
Section: Effects Of Orchestrating Productive Classroom Talk On Studen...mentioning
confidence: 99%